Unraveling Electra Complex in Kanza Javed’s Ashes, Wine and Dust - Raza, Maryam; Tahir, Athar (Journal of Communication and Cultural Trends, 2019)
The aim of this study is to explore the Jungian Electra complex in Kanza Javed’s Ashes, Wine and Dust. This is a qualitative research. Electronic media including reviews and interviews form the secondary source of this study. The researcher substantiates that Javed’s young protagonist Mariam Ameen is father-fixated for her beloved grandfather, who is simply known as Dadda. The concealed unconscious desire for her grandfather is unveiled by dint of establishing the fact that Dadda is the true father figure for Mariam. He overshadows the role of the biological father, taking up the position of an immediate father for Mariam. This accentuates the underlying Electra complex in Mariam’s heart. Moreover, the use of double roles is also deciphered as a leitmotif in Javed’s novel. Mariam serves as the doppelganger of Parakneeti which further aids the prevalence of the Electra complex. Dadda’s incessant influence in Mariam’s life even after his death and her self-imposed spinsterhood is discerned in terms of her infatuation for her grandfather. This study also analyses Mariam’s journey to the land of her grandfather as a metaphorical voyage of regression to the phallic stage which renders in a metaphysical union of the lover and the beloved. As a result, it is a journey of self-discovery in terms of love. The significance of this critical study is that it broadens the research horizons on Javed’s work as a psychoanalytic novel. It also enables the researchers to explore theories by other psychoanalysts, since only Freud and Jung share the limelight in the field of psychoanalytic research.